Static Modeling and Parameter Impact Analysis of the Bearing System in RV Reducers - Tang, Yingjian (International Journal of Mechanical and Electrical Engineering, 2026)
The RV reducer is a critical transmission component in industrial robot joints, whose bearing system’s mechanical performance directly affects the overall machine’s lifespan and reliability. This study establishes a complete static model of the RV reducer, incorporating deformation compatibility conditions and force equilibrium equations. Through numerical simulation, the effects of manufacturing errors and key structural parameters on bearing forces are analyzed. The results show that radial and angular errors significantly alter the load distribution on the crankpin bearings, increasing the force amplitude, while having minimal impact on the output bearings. Increasing the eccentricity reduces the maximum bearing force, whereas variations in the pin gear center circle radius have a relatively minor influence on the force trends. This research provides a theoretical basis for the design and performance optimization of RV reducers.